Respuesta :
Step-by-step explanation:
As instructed
Use Elimination Method....
2x - y = 2
2x - 2 = y
y = 2x - 2 ----------- equation 1
5x + y = -9
Substitute for y
5x + 2x - 2 = -9
7x = -9 + 2
7x = -7
x = -7/7
x = -1
Substitute for x in equation 1
y = 2x - 2
y = 2(-1) - 2
y = -2 - 2
y = -4
Answer:
(- 1, - 4 )
Step-by-step explanation:
Given the 2 equations
2x - y = 2 → (1)
5x + y = - 9 → (2)
Adding the 2 equations term by term will eliminate the y- term, that is
7x + 0 = - 7
7x = - 7 ( divide both sides by 7 )
x = - 1
Substitute x = - 1 into either of the 2 equations and solve for y
Substituting into (2)
5(- 1) + y = - 9
- 5 + y = - 9 ( add 5 to both sides )
y = - 4
solution is (- 1, - 4 )